Fostering Positive Citizenship Behavior through Satisfaction and Place Attachment: Insights from the Batu Street Food Festival - Sartika, Sartika; Kusumawati, Andriani; Anni Rahimah; Yusri Abdillah (Faculty of Economics, Universitas Sriwijaya, 2024)
This study aims to explore how memorable experiences shape citizenship behavior, with the specific purpose of understanding the psychological mechanisms that drive voluntary positive behaviors among festival visitors. Focusing on the Batu Street Food Festival, this research draws upon the Stimulus–Organism–Response (SOR) framework to examine the mediating roles of place attachment and satisfaction in connecting memorable experiences to citizenship behavior. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 222 festival attendees. The findings reveal significant positive relationships, showing that place attachment and satisfaction strengthen the impact of memorable experiences on behaviors. This research addresses theoretical gaps in the tourism literature and provides practical insights for enhancing visitor attachment at tourism festivals. While the study emphasizes the value of crafting meaningful experiences, its focus on a single festival highlights the need for further research in diverse contexts to validate and expand these findings.